Lived meanings of counterfeit branded fashion goods for everyday consumption - Rosely, Nurhidayah; Raja Yusof, Raja Nerina; Hashim, Haslinda; Abdullah Thani, Ayu Kamareenna (Human Resources Management Academic Research Society (HRMARS), 2024)
Due to the plethora of counterfeit goods in the physical and virtual marketplace, the plummeting demand for genuine fashion goods led to social and economic problems in the fashion goods industry. These dark markets pose the most critical challenge for luxury brand manufacturers in discouraging consumers from participating in counterfeiting activities. Based on a hermeneutic phenomenology study, this research attempted to examine an exhaustive and contextualised account of 12 consumers consumption experiences on the purchase of counterfeit branded fashion goods through in-depth interviews. The data were analysed using thematic analysis, and two themes emerged from this study; special occasions and prized collection. It validated that consumers refused to detach from the brand and purchased counterfeit branded fashion goods due to the intense attachment with the desired brand. It enables them to connect to the brand daily, which echoed profane consumption. The data confirmed how consumers treat the original branded fashion goods as sacred objects, even though the value should be preserved, and their involvement in counterfeit consumption was merely to protect those original branded fashion goods. This analysis adds knowledge to counterfeit branded fashion goods and consumer behaviour as the emerging themes depicted the actual experiences captured from the consumers who continuously involved in counterfeit consumption practice.